Dampak Kualitas Pelayanan Terhadap Kepuasan Pasien Puskesmas: Studi Literature - M Hasyrul Muchtar; Dety Mulyanti (Universitas Katolik Widya Karya Malang, 2023)
Quality of service caused by human resources, facilities, and referrals that are not optimal. This study aims to determine the effect of service quality on patient satisfaction at the Puskesmas. This type of research is quantitative research with associative methods. The population in this study were all visitors who came to the Puskesmas. Sampling was done by purposive sampling technique. The mnumber of samples used in this study were 100 respondents. The data collection technique used was a questionnaire with a Likert scale. The analysis technique was carried out using multiple regression analysis using SPSS. The results of the study show that the tangible dimension has a significant influence on patient satisfaction, the reliable dimension has a significant effect on patient satisfaction, the responsiveness dimension has a significant influence on patient satisfaction, the assurance dimension has a significant influence on patient satisfaction, the empathy dimension has a significant influence on patient satisfaction. The most dominant dimension of influence is tangible, while the lowest is responsiveness. Tangible, reliable, responsiveness, assurance and empathy dimensions simultaneously have a significant influence on patient satisfaction. The results of the study are expected that the management of the Banja Loweh Community Health Center, Fifty Cities District, will further improve service quality, especially on the lowest responsiveness dimension.